Evidence for the Fidelity and Effectiveness of Living Independent From Tobacco for People with Disabilities and Their Caregivers. (January 2019) - Havercamp, Susan M; Barnhart, Wesley R; Ellsworth, David; Coleman, Erica; Lorenz, Allison; Whalen Smith, Cara N; Riddle, Ilka K
People with disabilities (PWD) are more likely to use tobacco and less likely to access tobacco cessation programs compared with people without disabilities. Living Independent From Tobacco (LIFT), an evidence-based intervention designed for PWD, was piloted with dyads of PWD (n = 5) and their caregivers (n = 7). As an important source of practical and social support for PWD, caregivers also impact health-related attitudes, knowledge, and behaviors of PWD. Caregivers who smoke may unwittingly interfere with cessation efforts of the people they support. We found that LIFT could be offered to dyads of PWD and their caregivers with fidelity. The intervention was associated with increased use of coping strategies and self-efficacy to reduce smoking. Tobacco use decreased at post-test (−34.94%), with further reduction 6-months after the intervention (−50.60%). Implications for offering inclusive health promotion interventions to both PWD and their caregivers are discussed.